-7-6=x

Simple and best practice solution for -7-6=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-6=x equation:


Simplifying
-7 + -6 = x

Combine like terms: -7 + -6 = -13
-13 = x

Solving
-13 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-13 + -1x = x + -1x

Combine like terms: x + -1x = 0
-13 + -1x = 0

Add '13' to each side of the equation.
-13 + 13 + -1x = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -1x = 0 + 13
-1x = 0 + 13

Combine like terms: 0 + 13 = 13
-1x = 13

Divide each side by '-1'.
x = -13

Simplifying
x = -13

See similar equations:

| 10x-11x+3=0 | | -9-3=x | | n-9=-42 | | -5(6m-3)=38-7m | | -10+4x=-42 | | 0.88=log(x) | | 2(9x+631)=2x+270 | | .88=log(x) | | 1-5b-4b=10 | | 11z=-100 | | 3n-9+3=24 | | 3(14-4y)-5y=-9 | | 6y+5=10y-1 | | 12k+14=10k-2k-7 | | -3(x+4)+16= | | J-8=-5 | | 10x-8=31.5 | | 2(2x-11)=2x | | 8x-4+8x-4+21+3=180 | | 9x^2-42x+37=0 | | 11-3(x+4)+5= | | H-41=13 | | 24=3(x)-6 | | (10x+36y)+(2x+y)= | | 63=60.50p+17.50 | | 8x-4+8x-4+4+3=180 | | 9=3(x)-6 | | 152+8h= | | 19=b-3 | | -3=3(x)-6 | | -6.5z+7.5z= | | 4n-2=12-4n |

Equations solver categories